Prediction value of anti-Mullerian hormone (AMH) serum levels and antral follicle count (AFC) in hormonal contraceptive (HC) users and non-HC users undergoing IVF-PGD treatment. (3rd October 2017) - Bas-Lando, Maayan; Rabinowitz, Ron; Farkash, Rivka; Algur, Nurit; Rubinstein, Esther; Schonberger, Oshrat; Eldar-Geva, Talia
Abstract: Use of hormone contraceptives (HC) is very popular in the reproductive age and, therefore, evaluation of ovarian reserve would be a useful tool to accurately evaluate the reproductive potential in HC users. We conducted a retrospective cohort study of 41 HC users compared to 57 non-HC users undergoing IVF-preimplantation genetic diagnosis (PGD) aiming to evaluate the effect of HC on the levels of anti-Mullerian hormone (AMH), small (2–5 mm), large (6–10 mm) and total antral follicle count (AFC) and the ability of these markers to predict IVF outcome. Significant differences in large AFC ( p  = 0.04) and ovarian volume ( p  < 0.0001) were seen, however, there were no significant differences in small and total AFC or in serum AMH and FSH levels. Oocyte number significantly correlated with AMH and total AFC in HC users ( p  < 0.001) while in non-HC users these correlations were weaker. In HC users, the significant predictors of achieving <6 and >18 oocytes were AFC (ROC-AUC; 0.958, p  = 0.001 and 0.883, p  = 0.001) and AMH (ROC-AUC-0.858, p  = 0.01 and 0.878, p  = 0.001), respectively. The predictive values were less significant in non-HC users. These findings are important in women treated for PGD, in ovum donors and for assessing the fertility prognosis in women using HC and wishing to postpone pregnancy.